Associations of alcohol use and smoking with early-onset colorectal cancer: a systematic review and meta-analysis - Wieser, Janine; Hoffmeister, Michael; Brenner, Hermann; Mons, Ute (Clinical colorectal cancer and other gastrointestinal malignancies, 2025)
The incidence of early-onset CRC (EOCRC) has lately been increasing. We aimed to synthesize findings on the association of smoking and alcohol consumption with EOCRC in a systematic review and meta-analysis. Following preregistration of the study protocol in PROSPERO (CRD42023424149), we searched PubMed and Web of Science for observational studies on the association of smoking or alcohol consumption with EOCRC. We performed meta-analyses, including several subgroup analyses, to examine the association of alcohol consumption and smoking, respectively, with the risk of EOCRC. Generally, random effects models were calculated, with fixed effect models employed for analyses including only a small number of studies. We included eleven studies for alcohol consumption and twelve for smoking. Alcohol use was found to be a risk factor for EOCRC, with a pooled odds ratio (OR) of 1.39 (95% confidence interval (CI) 1.14-1.69). A dose-response model revealed a positive association between the amount of ethanol consumed and the risk of EOCRC (OR per 10 g/d ethanol increase 1.02, 95% CI, 1.01-1.08). Smoking (ever or current combined) was also found to be a significant risk factor for EOCRC (OR 1.39, 95% CI, 1.20-1.59). Alcohol consumption and smoking are significant risk factors for EOCRC and should be addressed in the context of prevention.
Online veröffentlicht: 28. Mai 2025, Artikelversion: 14. August 2025
Gesehen am 10.12.2025